2020
DOI: 10.1097/jom.0000000000002125
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Health Risks Among Firefighters; The New Jersey Firefighter Health Survey

Abstract: Objective: There is a growing literature on the risk of chronic disease among firefighters, including cardiovascular disease (CVD) and cancer. However there is little information on firefighter's perception thereof. Methods: Firefighters attending a union convention in New Jersey completed a survey with four domains: firefighting experience; perceived additional risk for chronic diseases (six-point Likert scale); cancer screening history; demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Like respiratory and heart diseases, many firefighters also identify cancer as a major health concern, 1,2,11,14 which was reflected in the number of presumption claims filed for cancers. The high acceptance rate among presumption cancer claims (86%) is likely because of the Washington law specifically defining 11 types of cancer eligible for presumptive coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Like respiratory and heart diseases, many firefighters also identify cancer as a major health concern, 1,2,11,14 which was reflected in the number of presumption claims filed for cancers. The high acceptance rate among presumption cancer claims (86%) is likely because of the Washington law specifically defining 11 types of cancer eligible for presumptive coverage.…”
Section: Discussionmentioning
confidence: 99%
“…While some cancers (such as mesothelioma) have received considerable attention, today there is growing recognition of the dangers of multiple types of cancers among firefighters. Specifically, studies have found linkages between firefighting and numerous cancers, for example, bladder, 4,5,6 colorectal, 7,8 brain and central nervous system, 9,10 non-Hodgkin's lymphoma, 5,11,12 skin melanoma, 4,5,13 prostate and testicular, 5,13,14 with most having an increased mortality rate when compared to the general population. 4 Kidney cancer has also been found at increased rates, however, findings are less consistent for kidney cancer and certain other cancers, including Hodgkin's lymphoma, 2,11,12 leukemia, 4,15,16 lymphosarcoma and reticulosarcoma, 4 multiple myeloma, 4,17,18 and pancreatic cancer.…”
Section: Cancers and Rates Of Occurrencementioning
confidence: 99%
“…Research shows that firefighters have general concerns about cancer risk, 39 with both new and experienced firefighters perceiving cancer as main health risk. 40 Recent studies show that firefighters believe they are at higher risk of cancer than the general public, 9 and believe those risks are high to very high for colon, pulmonary, hematologic, breast, prostate, testicular, lung, oral, and all cancers, 9 with female firefighters expressing specific concerns about breast cancer as a result of beliefs that breast tissue is the most absorbent part of the body and that gear opens in such a way as to increase exposure. 41 Concerns about cancer risk are true both of career urban firefighters in the U.S. 39,40,42,9,43, rural volunteer and career firefighters in the U.S., 44 female firefighters, 41 and firefighters in the Dominican Republic.…”
Section: Cancer Risk Perceptions and Knowledgementioning
confidence: 99%
“…16 In addition to the multiple physical hazards, firefighters also face some unique psychosocial stressors, frequently working 24-or 48-hour shifts during which they remain and away from their homes and on-call for unpredictable events. 17,18 Taken together, these occupational health risks reflect a significant burden, and although the individual risks have been welldescribed, the ways some of these factors interact have yet to be fully explored.…”
mentioning
confidence: 99%